Feeling and Moral Motivation in Kant: A Response to the Frierson-Grenberg Debate - K. Radhakrishnan, Vivek (Con-Textos Kantianos. International Journal of Philosophy, 2023)
In this paper, I aim to resolve the Frierson-Grenberg debate on the nature of Kant’s account of moral motivation that took place in the third issue of Con-textos Kantianos. In their respective interpretations, Frierson and Grenberg fail to accommodate the a priori status of moral feeling when incorporating it into Kant’s moral motivational structure. In response, I provide a novel transcendental interpretation – one that takes the a priori moral feeling both as an incentive of morality and as that which conditions the possibility of morality in human agents. I argue that Kant developed the notion of moral feeling solely in order to resolve the problem of motivational skepticism concerning the moral law. Since this problem occurs as a part of Kant’s search for the supreme principle of morality, the notion of moral feeling becomes a part of both Kant’s moral motivational structure and his argument to justify the moral law.